Mixing characteristics of multiple impacting jets - Chew, Jia Bei. (2013)
Experiments using one and three identical round turbulent jets were performed in still non-buoyant conditions. The single jet flow and triple-jet flow produced by two jets on either side of a central jet at a converging ratio of 45° have been characterised using Particle Image Velocimetry (PIV) and flow imaging software. Normalisation of the flow and comparison of the tri-jet flows were accomplished